The Effect of the Proportion of Ginger and Spices Extracts and the Addition of Sugar on the Physicochemical Properties of Instant Spiced Coffee - Sania Khoiri Rahma; Ulya Sarofa; Riski Ayu Anggreini (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Coffee is a refreshing beverage which loved by any community. The addition of spices to coffee enhances the health benefits. Spices used are ginger, galangal, lemongrass, pandanus, and cinnamon. Instant spice coffee may be created through crystallization with sugar as a crystallizing agent. This study used Completely Randomize Design (CRD) from a two-factor factorial pattern. Factor I is the proportion of ginger and spice extract (2:8, 3:7, and 4:6), and factor II is the additional sugar (25.35%, and 45%). The data was analyzed using the Analysis of Variance (ANOVA) and the Duncan Multiple Range Test (DMRT) follow-up tests at a 5% level. The best treatment is combining the proportion of ginger and spice extract 4:6 with the addition of 45% sugar that produces instant spice coffee with a yield of 37,73%, water level 1.32%, ash level of 1.39%, solubility of 93.13 %, soluble speed 0.14g/s, total soluble solids of 17.15% brix, antioxidant activity of 85.66%, total phenol of 15.43 mgGAE/g.